2004
DOI: 10.2165/00126839-200405040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sulphonylurea Glibenclamide on Liver and Kidney Antioxidant Enzymes in Streptozocin-Induced Diabetic Rats

Abstract: Administration of glibenclamide to diabetic rats reversed diabetes-induced changes, suggesting that glibenclamide may directly increase liver CAT and SOD activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 6 publications
8
26
0
1
Order By: Relevance
“…A study strongly supported the present data that the body weight of glibenclamide treated diabetic rats showed a significant reduction when compared with the healthy groups [37] . Hyperglycaemia-induced groups showed a rapid reduction in the body weight which was similar to the finding reported by Gandhi and Sasikumar [38] .…”
Section: Resultssupporting
confidence: 90%
“…A study strongly supported the present data that the body weight of glibenclamide treated diabetic rats showed a significant reduction when compared with the healthy groups [37] . Hyperglycaemia-induced groups showed a rapid reduction in the body weight which was similar to the finding reported by Gandhi and Sasikumar [38] .…”
Section: Resultssupporting
confidence: 90%
“…The decreased levels of renal and hepatic SOD activity of HyGR showed evidence of restoration of the enzyme activity that were comparable to NORM rats following the administration of the various experimental herbal formulations ( Figure 2). The present findings are comparable with previous report 25 in which they noted that glibenclamide directly increased renal and hepatic CAT and SOD activities of S-IDR. Reports have shown that ethanolic extract of Sphaeranthus indicus exhibited protective effect against lipid peroxidation and normalized repressed SOD, CAT, glutathione S-transferase activities in gentamicin induced nephrotoxic rats.…”
Section: -21supporting
confidence: 93%
“…Superoxide dismutase activity in diabetes has been shown to decrease (19), remain unchanged (20), and even increase (21). Increased O 2 production leads to an initial increase in SOD activity, whereas glycosylation of the enzyme and/or hydrogen peroxide (H 2 O 2 ) accumulation decreases SOD activity.…”
Section: Discussionmentioning
confidence: 99%